Bowhead whale foraging dives are defined by speed and body orientation - Manon F. den Haan; Paolo S. Segre; Eric Kilabuk; Mason Agnakak; Fred Dialla; Sarah M. E. Fortune (PLoS ONE, 2026)
Quantifying the time baleen whales spend foraging is central to understanding the extent to which climate driven shifts in low-trophic prey may affect energy acquisition. To date, the most comprehensive understanding of balaenid (bowhead and right whale) feeding behavior comes from studies using inertial sensing tags (biologgers). Here, periods of ram filtration were inferred under predictable foraging conditions where whales targeted a deep, diapausing prey layer. However, foraging conditions are increasingly variable in high latitudes and zooplankton vertical distribution, abundance and biomass vary seasonally based on ontogenetic migration. Our objective was to identify the kinematic features of confirmed bowhead feeding in a sub-Arctic fjord where prey availability fluctuates with tidal cycles, by collecting high-resolution, 3D biologging data (Customized Animal Tracking Solutions Tags) and concurrent video recordings for behavioral validation. Using a mixed-model approach we found that mean bottom speed, bottom pitch and roll, change in average swim speed and time of day were the best predictors of bowhead whale feeding. Consistent with previous studies, fluke stroke frequency was significantly faster when feeding (0.191 Hz ± 0.045 SD) compared with not-feeding (0.172 Hz ± 0.037 SD). However, we observed a depth-dependent switch in fluke stroke frequency, whereby the fluking rate was higher (0.192 Hz ± 0.039 SD) at shallow depths (≤23 m) and lower (0.151 Hz ± 0.024) at deeper depths (>23 m). Observed shifts in fluke stroke frequency may be attributed to physical forces acting in the upper water column such as buoyancy, drag and tidal forces. By using the descriptive kinematic variables, we can better identify feeding behavior in kinematic data from balaenids and improve our understanding of foraging efforts of bowhead whales in a changing climate, particularly since dive shape alone may overestimate feeding activities.